EFFECTIVE TECHNIQUES OF CHILDREN WITH DOWN SYNDROME’S SPEECH DEVELOPMENT (Psychology Travelogs, 2022)
The article is devoted to the problem of language acquisition and speech development of children with Down syndrome. This will give such a child the opportunity to socialize in a team and feel like a full member of society. The necessity and importance of children with Down syndrome speech development are substantiated. The peculiarities of the structure of the speech apparatus of a child with Down syndrome and speech problems that arise due to the peculiarity of the structure of the speech apparatus and the main developmental disorders in general are presented. The advantages of the specifics of children with Down syndrome communicative activity (friendliness, contact, desire to communicate and social interaction) are determined. This requires the search for modern effective correction techniques that facilitate this process. Methods of working with children with Down syndrome are based on the laws of child development, the peculiarities of Down syndrome development, as well as a particular child’s features and level of development. Such techniques today are «Little Steps», methods of speech development and reading instruction by Romena Augustova, means of alternative and supportive communication, «Look and learn. Language and Reading», as well as the program for speech means of communication formation «We start talking». A brief overview of these tecniques, content, aim and purpose, advantages, disadvantages, features of their implementation were given However, the study does not cover all aspects of the problem we raised. The prospect of further research may, in our opinion, be the professional development of guidelines for specialists in special and inclusive education, teachers and parents of children with Down syndrome on the use of corrective methods of speech development of this category of children in correctional, educational, extracurricular activities and at home.
Keywords: Down syndrome; child with Down syndrome; language; speech; speech development; psychocorrectional techniques; techniques of speech development